Lavado Correcto de las Manos para Manipuladores de Productos Frescos - Amy Simonne; Mark Ritenour; Jeff Brecht; Steve Sargent; Keith Schneider (EDIS)
This document is FCS8762-Span, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: March 2004.